Physiological comparison between competitive and beginner high intensity functional training athletes - Adami, P. E.; Rocchi, J. E.; Melke, N.; Macaluso, A. (Journal of Human Sport & Exercise, 2022)
Introduction: Among high intensity trainings, high intensity functional training (HIFT) represent one of the most recent developments. The aim of the present study was to investigate the differences between a group of competitive (CMP) HIFT athletes and a group of age- and gender-matched beginner (BGN) HIFT athletes, to clarify the physiological characteristics of each group and the reasons for differences.